CREATING A BUDGET FOR THE CURRENT STAGE OF DEVEL OPMENT OF THE RUSSIAN ECONOMY - Andrey A. Derkach (Статистика и экономика)
The article discusses the methodology ofthe budget in terms of innovative development of the Russian economy. Explored approaches to evaluating the effectiveness of public investment. The features of the use of resources of the Investment budget in innovative software industry asthe social sphere and the real economy